Proximal Policy Based Deep Reinforcement Learning Approach for Swarm Robots - Tan, Ziya; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2021)
Artificial intelligence technology is becoming more active in all areas of our lives day by day. This technology affects our daily life by more developing in areas such as industry 4.0, security and education. Deep reinforcement learning is one of the most developed algorithms in the field of artificial intelligence. In this study, it is aimed that three different robots in a limited area learn to move without hitting each other, fixed obstacles and the boundaries of the field. These robots have been trained using the deep reinforcement learning approach and Proximal policy optimization (PPO) policy. Instead of uses value-based methods with the discrete action space, PPO that can easily manipulate the continuous action field and successfully determine the action of the robots has been proposed. PPO policy achieves successful results in multi-agent problems, especially with the use of the Actor-Critic network. In addition, information is given about environment control and learning approaches for swarm behavior. We propose parameter sharing and behavior-based method for this study. Finally, trained model is recorded and tested in 9 different environments where the obstacles are located differently. With our method, robots can perform their tasks in closed environments in the real world without damaging anyone or anything. © 2021 IEEE.
2021 Zooming Innovation in Consumer Technologies Conference, ZINC 2021 -- 26 May 2021 through 27 May 2021 -- Novi Sad -- 171215
Keywords: deep learning; deep reinforcement learning; swarm behavior